Stem hydraulic architecture and xylem vulnerability to cavitation for miombo woodlands canopy tree species - Vinya, R (2010)
Africa's miombo woodlands constitute one of the most important dry tropical forests on earth, yet the hydraulic function of these woodlands remains poorly researched. Given the current predictions of increased aridity by the end of this century in the miombo ecoregion, understanding the likely response of miombo woodlands tree species to water stress is crucial in planning adaptation strategies. Predicting the response of miombo woodlands to future climate trends is hampered by a lack of knowledge on the physiology of the common miombo woodlands tree species. In particular, plant-water relations for this woodlands type are not well understood. An understanding of plant-water relations for this woodlands type will provide insights into how water limits tree species distribution in this ecosystem. This will also improve our prediction model on the likely response of this ecosystem to predicted climate change. For this reason, the overall objective of this research was to evaluate the hydraulic architecture and xylem vulnerability to cavitation for nine principal miombo woodlands tree species differing in drought tolerance ability and habitat preference. This was achieved by; examining the hydraulic properties and evaluating the extent to which each hydraulic design was vulnerable to water stress-induced xylem cavitation; investigating how seasonal changes in plant-water relations influences seasonal patterns of leaf display and; analyzing the relationship between stem hydraulic supply and leaf functional traits related to drought tolerance ability. This research has found that drought-intolerant tree species with mesic specialization have more efficient stem hydraulic systems than co-occurring habitat broad ranging species. Broad ranging tree species attain wider habitat distribution by adjusting their hydraulic supply in response to changing ecosystem water availability. The finding that hydraulic properties differ significantly between tree species with contrasting habitat preference suggests that tree hydraulic design may have some adaptive ecological role in influencing species habitat preferences in miombo woodlands. The evaluation of xylem vulnerability to cavitation revealed that mesic specialized tree species were more vulnerable to water stress-induced cavitation than habitat broad ranging tree species. Vulnerability to cavitation in individuals from the same broad-ranging species growing in contrasting habitats showed only marginal and statistically insignificant (P > 0.05) differences between wet and dry sites. In the investigation of the influence of seasonal changes in stem water relations on seasonal leaf display, seasonal rhythms in stem water status were found to exert significant controls on leaf phenology. Mesic specialists had strong stem water controls throughout the year in comparison to broad ranging tree species. An analysis of the relationship between stem hydraulic supply and leaf functional traits suggests that stem hydraulic supply constrains leaf biomass allocation patterns among miombo tree species. Mesic specialists tend to invest more in leaf longevity than broad ranging tree species. This thesis has uncovered some interesting relationships between plant-water-relations and the distribution of miombo woodlands tree species. These results lead to the conclusion that in an event of increased ecosystem drying under future climate trends, tree species with mesic specialisation are at a greater risk of experiencing cavitation related species mortality than broad ranging ones.